Pengaruh Kepemilikan Keluarga terhadap Profitabilitas dengan Firm Age, Firm Size, dan Leverage sebagai Variabel Kontrol - Hizkia Leonard Pah; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This research aimed to analyze the affect of family ownership to profitability with firm age, firm size, and leverage as the control variables. Profitability as dependent variable measured by ROA, family ownership as the independent variable, and firm age, firm size, and leverage as the control variables. This research was conducted on the firms on all sectors, listed in Indonesian Stock Exchange during the period of 2012 – 2015 with a sample of 357 firm. This research used regression analysis panel data that analysid with Eviews software version 6.0The result of this study indicated that, family ownership had no significant affect on profitability, firm age had positive and significant affect on profitability, firm size had positive and significant on profitability, and leverage had no positive and significant on profitability.